Quantifying the impact of rising food prices on child mortality in India: A cross-district statistical analysis of the District Level Household Survey - Fledderjohann, J; Vellakkal, S; Khan, Z; Ebrahim, S; Stuckler, D (Oxford University Press, 2016)
Background: Rates of child malnutrition and mortality in India remain high. We tested the hypothesis that rising food prices are contributing to India’s slow progress in improving childhood survival. Methods: Using Rounds 2 and 3 (2002-2008) of the Indian District Level Household Survey, we calculated neonatal, infant, and under-five mortality rates in 364 districts, and merged these with district-level food price data from the National Sample Survey Office. Multivariate models were estimated, stratified into 27 less deprived states and territories and 8 deprived states (‘Empowered Action Groups’). Results: Between 2002 and 2008, the real price of food in India rose by 11.7%. A 1% increase in total food prices was significantly associated with a 0.49% percent increase in neonatal (95% CI: 0.13% to 0.85%), but not infant or under-five mortality rates. Disaggregating by type of food and level of deprivation, in the 8 deprived states, we found an elevation in neonatal mortality rates of 0.33% for each 1% increase in the price of meat (95% CI: 0.06% to 0.60%) and 0.10% for a 1% increase in dairy (95% CI: 0.01% to 0.20%). We also detected a significant adverse association of the price of dairy with infant (b=0.09%; 95% CI: 0.01% to 0.16%) and under-five mortality rates (b=0.10%; 95% CI: 0.03% to 0.17%). These associations were not detected in less deprived states and territories. Conclusions: Rising food prices, particularly of high-protein meat and dairy products, were associated with worse mortality outcomes. These adverse associations were concentrated in the most deprived states.